Conjunto de bases universal para os átomos de H até Ar - Nascimento, Jeniffer Alessandra Ribeiro do (2011)
A universal Gaussian basis set for the atoms H to Ar is presented. From a single sequence of 17 Gaussian exponents, generated using the Generator Coordinate Hartree Fock method, subsets were chosen to compose the Gaussians of each symmetry of each atom of H through Ar, following similar procedure to that used in the generation of Universal Gaussian Basis Set of de Castro and Jorge (1998). Then the exponents with smaller contribution to the Hartree-Fock (HF) total energy were removed in order to reduce the size of the atomic basis. The resulting universal basis set was used to calculate the HF total energies and comparisons were made with Numerical HF results. The U17 set has been augmented with diffuse and polarization functions, respectively extracted of the DZP and ADZP basis sets and calculations of total energies and electric dipole moments for a group of diatomic molecules, we performed. The results obtained with the U17 augmented set were compared with other theoretical and experimental results.